Assessment and comparison of rhizosphere communities in cultivated Vaccinium spp. provide a baseline for study of causative agents in decline - Kawash, Joseph; Oudemans, Peter V.; Erndwein, Lindsay; Polashock, James J. (Frontiers in Plant Science, 2023)
It has long been recognized that the community of organisms associated with plant roots is a critical component of the phytobiome and can directly or indirectly contribute to the overall health of the plant. The rhizosphere microbial community is influenced by a number of factors including the soil type, the species of plants growing in those soils, and in the case of cultivated plants, the management practices associated with crop production. Vaccinium species, such as highbush blueberry and American cranberry, are woody perennials that grow in sandy, acidic soils with low to moderate levels of organic matter and a paucity of nutrients. When properly maintained, fields planted with these crops remain productive for many years. In some cases, however, yields and fruit quality decline over time, and it is suspected that degenerating soil health and/or changes in the rhizosphere microbiome are contributing factors. Determining the assemblage of bacterial and fungal microorganisms typically associated with the rhizosphere of these crops is a critical first step toward addressing the complex issue of soil health. We hypothesized that since blueberry and cranberry are in the same genus and grow in similar soils, that their associated rhizosphere microbial communities would be similar to each other. We analyzed the eukaryotic (primarily fungal) and bacterial communities from the rhizosphere of representative blueberry and cranberry plants growing in commercial fields in New Jersey. The data presented herein show that while the bacterial communities between the crops is very similar, the fungal communities associated with each crop are quite different. These results provide a framework for examining microbial components that might contribute to the health of Vaccinium spp. crops in New Jersey and other parts of the northeastern U.S.